2018
DOI: 10.1152/ajprenal.00292.2018
|View full text |Cite
|
Sign up to set email alerts
|

MAGI-2 and scaffold proteins in glomerulopathy

Abstract: In many cells and tissues including the glomerular filtration barrier (GFB), scaffold proteins are critical in optimizing signal transduction by enhancing structural stability and functionality of their ligands. Recently, mutations in scaffold protein Membrane-Associated Guanylate Kinase Inverted 2 (MAGI-2) encoding gene were identified among the etiology of steroid-resistant nephrotic syndrome (SRNS). MAGI-2 interacts with core proteins of multiple pathways such as TGF-β signaling, planar cell polarity pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 99 publications
2
18
0
Order By: Relevance
“…26,27 As the previous studies showed, the function of MAGI-2 for the SDs remains obscure. 28 Our study has revealed that MAGI-2 orchestrates the localization of Nephrin and Neph1 through PDZ domains together with other scaffold proteins (Figure 8). In other words, MAGI-2 plays a critical role in stabilizing the glomerular filtration barrier as a scaffold protein.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…26,27 As the previous studies showed, the function of MAGI-2 for the SDs remains obscure. 28 Our study has revealed that MAGI-2 orchestrates the localization of Nephrin and Neph1 through PDZ domains together with other scaffold proteins (Figure 8). In other words, MAGI-2 plays a critical role in stabilizing the glomerular filtration barrier as a scaffold protein.…”
Section: Discussionmentioning
confidence: 81%
“…Membrane-associated guanylate kinase inverted 2 (MAGI-2) is also one of the scaffold proteins identified in neuronal spines and podocytes. [26][27][28] It is already been established that MAGI-2 mediates the signaling of G protein-coupled receptors, RhoA, and Ras-associated protein-1. [29][30][31] Previously, we reported that podocyte-specific MAGI-2 knockout (KO) mice exhibit glomerulosclerosis and kidney failure in a manner similar to FSGS.…”
Section: Introductionmentioning
confidence: 99%
“…However, no previous studies have found associations between APOBEC3 and AD. MAGI2 regulates apoptosis, cytoskeletal reorganization, and glomerular development and is broadly expressed in the brain, thyroid, and 16 other tissues, including blood [32]. MAGI2 is a candidate gene associated with multiple phenotypes, as demonstrated by Alzheimer's Disease Neuroimaging Initiative genetic studies [33].…”
Section: Discussionmentioning
confidence: 99%
“…Because MAGI2 binds b-catenin at adherence junctions, 43,44 it has been suggested that MAGI2 could modulate Wnt/b-catenin signaling. 45 Pharmacological activation of b-catenin induced albuminuria in wild-type mice but not in b-catenin-KO littermates. 46 As shown in Con8 rat mammary epithelial tumor cells, dexamethasone prevents b-catenin phosphorylation and recruits it from the nucleus to adherence junctions.…”
Section: Discussionmentioning
confidence: 99%